2022
DOI: 10.1093/fampra/cmac115
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ perceptions of pharmacists working in general practice: a qualitative interview study

Abstract: Background Pharmacists are being increasingly employed as part of general practice teams globally, and their input has been associated with several clinical and economic benefits. However, there is a paucity of research focussing on general practitioners’ (GPs’) perceptions of pharmacist integration into practices in countries where this novel role for pharmacists is yet to become commonplace. Objective To explore GPs’ percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In the UK, the role of pharmacists in primary care is established, and in Ireland pilot studies of GP-based pharmacists have been conducted [ 44–46 ]. Recent research with GPs in Ireland indicates that there is an interest and appetite for the introduction of clinical pharmacists in General Practice [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the role of pharmacists in primary care is established, and in Ireland pilot studies of GP-based pharmacists have been conducted [ 44–46 ]. Recent research with GPs in Ireland indicates that there is an interest and appetite for the introduction of clinical pharmacists in General Practice [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey content was based on the results of a qualitative evidence synthesis [ 10 ] and a TDF-informed interview study [ 12 ]; therefore, this study was able to explore the causal determinants of GPs’ perceptions of pharmacist integration into general practice to inform future interventions better. While the survey utilised a multi-modal dissemination approach to enhance its reach and response rate, responses received via electronic routes could have been more extensive in number.…”
Section: Discussionmentioning
confidence: 99%
“…The survey (Supplementary File 1 ) was initially constructed based on the findings from a qualitative evidence synthesis [ 10 ] and a semi-structured interview study that utilised the Theoretical Domains Framework (TDF) as part of its methods [ 11 , 12 ]. The survey was then reviewed and further developed by consensus discussion amongst research team members, which consisted of three pharmacists (two practising) and two practising GPs.…”
Section: Methodsmentioning
confidence: 99%
“…This study identified barriers to collaboration between the pharmacist and other health professionals in general practice teams [ 26 , 32 – 34 ]. As general practices have busy schedules, most professionals did not have quality time to interact with the pharmacists and they had relatively limited awareness of the activities that pharmacists could perform in general practice [ 35 ]. Furthermore, interviews and survey findings highlighted that the pharmacists were more active than the GPs in contributing to relationship initiation.…”
Section: Discussionmentioning
confidence: 99%